CULTURAL SIGNIFICANCE AND HISTORICAL EVOLUTION OF CENTRAL ASIAN NATIONAL COSTUMES (THE CASE OF HEADDRESSES) - Mamatova, Zarrina Shodimurodovna (PT. Antis International Publisher, 2024)
General Background: National costumes are crucial cultural artifacts that reflect the historical and social fabric of societies. In Central Asia, these traditional garments offer significant insights into regional customs and social structures. Specific Background: Despite their importance, there is a limited understanding of how Central Asian national costumes, particularly headdresses, embody and communicate cultural values and traditions. Previous research has often overlooked the nuanced relationship between these garments and local customs. Knowledge Gap: There is a notable gap in comprehensive studies that link the cultural and symbolic significance of national costumes with their historical evolution and contemporary relevance, particularly in the context of tourism and cultural preservation. Aims: This study aims to explore the cultural significance and historical evolution of Central Asian national costumes, focusing on their relationship with life customs and traditions. It employs a mixed-methods approach to address existing knowledge gaps. Results: The research reveals that traditional headdresses in Central Asia carry deep symbolic and functional meanings, with distinct styles reflecting regional identities and social hierarchies. The analysis demonstrates a rich tapestry of cultural heritage and artistic expression inherent in these garments, highlighting both their unity and diversity. Novelty: By integrating qualitative and quantitative data from surveys, literature reviews, archival research, and official tourist websites, this study offers a comprehensive perspective on the role of national costumes in Central Asia. It provides new insights into the interplay between tradition, identity, and tourism. Implications: The findings underscore the importance of preserving and promoting traditional clothing as a vital component of Central Asia's cultural heritage. They suggest that national costumes play a significant role in enhancing cultural tourism and preserving regional identities, thus contributing to the broader field of cultural preservation and tourism development.